2003
DOI: 10.1080/03008200390223909
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Mechanical Stretching of Human Tendon Fibroblasts Increases the Production of Prostaglandin E 2 and Levels of Cyclooxygenase Expression: A Novel In Vitro Model Study

Abstract: Prostaglandin E(2) (PGE(2)) is a known inflammatory mediator of tendinitis, for which mechanical loading on tendons is believed to be one of the most prominent causation factors. Previous in vitro studies have shown that cyclic mechanical stretching of cells can cause changes in cell morphology and alteration of both DNA and protein syntheses. In our study, a novel system was used whereby tendon fibroblasts are cultured on microgrooved silicone surfaces and are subjected to cyclic uniaxial stretching along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 27 publications
7
94
0
2
Order By: Relevance
“…Besides IL-1β, PGE 2 is another major catabolic factor that is considered to be involved in the development of tendinopathy and joint diseases (Almekinders et al, 1993;Laufer, 2003;Wang et al, 2003Wang et al, , 2004. Previously, it was shown that tendon fibroblasts under repetitive uniaxial mechanical stretching at 8% and 12% strains increased COX-2 expression and release of PGE 2 (Wang et al, 2003).…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides IL-1β, PGE 2 is another major catabolic factor that is considered to be involved in the development of tendinopathy and joint diseases (Almekinders et al, 1993;Laufer, 2003;Wang et al, 2003Wang et al, , 2004. Previously, it was shown that tendon fibroblasts under repetitive uniaxial mechanical stretching at 8% and 12% strains increased COX-2 expression and release of PGE 2 (Wang et al, 2003).…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 99%
“…Previously, it was shown that tendon fibroblasts under repetitive uniaxial mechanical stretching at 8% and 12% strains increased COX-2 expression and release of PGE 2 (Wang et al, 2003). Microsomal PGE synthase type 1 (mPGES-1), which is involved in the conversion of PGH 2 to PGE 2 , is an inducible enzyme functionally linked to COX-2.…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 99%
“…The protocol for obtaining tendon samples was approved by the University of Pittsburgh Institutional Review Board. HPTFs were isolated and maintained in Dulbecco's Modified Eagle Medium (DMEM) containing 10% FBS, penicillin (50 U/ml), and streptomycin (50 U/ml) as previously described (Wang et al, 2003). The fibroblasts were subcultured for 4-6 passages and were used for the experiments.…”
Section: Cell Culturementioning
confidence: 99%
“…Tendon inflammation is marked by the presence of inflammatory mediators, including prostaglandin E 2 (PGE 2 ) and leukotriene B 4 (LTB 4 ) (Almekinders et al, 1993). Although the exact amounts of both PGE 2 and LTB 4 in inflamed tendons are not known, their levels are markedly increased when tendons or tendon fibroblasts are subjected to repetitive mechanical loading conditions (Langberg et al, 1999;Wang et al, 2003;Li et al, 2004). These data suggest that PGE 2 and LTB 4 may play a role in tendon degeneration, the late stages of tendinopathy (Wang, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical histopathologic findings demonstrate altered expression of several collagenases in tendinopathy [16,27,32,33], while animal exercise and overuse have produced both inflammatory and degenerative changes in tendons [5,9,29,34,38]. Similarly, mechanical overloading of tendon explants [13,15] and tendon cells [2,4,8,26,36,41,45,46] in vitro led to increases in both collagenase and inflammatory mediators, in conjunction with a loss of mechanical integrity. MMP-13 (collagenase-3), which has been implicated in osteoarthritis, rheumatoid One or more of the authors (HBS, MBS, ELF) has received funding from the National Institutes of Health.…”
Section: Introductionmentioning
confidence: 98%